Investigating nursing staff attitude and coping strategies on deliberate self-harm in patients diagnosed with personality disorders or intellectual disabilities and who are situated within medium-secure hospitals within the United Kingdom - Inger, James Alexander (2018)
Psychiatric nursing staff (N=139) working within UK medium-secure hospitals participated in exploring attitude and coping strategies towards deliberate self-harm within in-patients diagnosed with either an Intellectual Disability or Personality Disorder. Additionally, this study explored whether coping strategies, age, gender, job-role and length of experience influenced attitude. Using online surveys, the Ways of Coping Questionnaire and Attitudes Towards Deliberate Self-Harm Questionnaire (Dutch-Version) were administered. Results found that staff were negative towards self-harm and that two styles of coping strategies were significantly found. Seeking Social Support was significant for staff working with patients diagnosed with Personality Disorders, whereas Problem-Solving was significant for those working with Intellectual Disabilities. No significance was found between age, gender, job-role or length of experience. A significant regression was found between coping strategies and attitude, which accounted for 22.2% variation. Confrontative Coping strategy was found to be the only significant, positive relationship towards staff attitude.